2018
DOI: 10.21839/jaar.2018.v3is1.165
|View full text |Cite
|
Sign up to set email alerts
|

Impact of modern technology in education

Abstract: Technology is a gift of God. After the gift of life it is perhaps the greatest of God's gifts. It is the mother of civilizations, of arts and of sciences. Technology has certainly changed the way we live. It has impacted different facets of life and redefined living. Undoubtedly, technology plays an important role in every sphere of life. Several manual tasks can be automated, thanks to technology. Also, many complex and critical processes can be carried out with ease and greater efficiency with the help of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
393
2
43

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 539 publications
(445 citation statements)
references
References 0 publications
7
393
2
43
Order By: Relevance
“…Humans are becoming more dependent on technology and spend more time on the mobile and internet (Elsobeihi & Naser, 2017). In education field, it was revealed that modern equipment technology and tools make students' learning and interactivity improves (Raja & Nagasubramani, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Humans are becoming more dependent on technology and spend more time on the mobile and internet (Elsobeihi & Naser, 2017). In education field, it was revealed that modern equipment technology and tools make students' learning and interactivity improves (Raja & Nagasubramani, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has worked out to be simpler for teachers to get the learning of personal computers (PC) in teaching. The business of technology in the area of education is four-overlap: it is incorporated as a part of the educational programs, and instructional delivery framework, a method for holding instructions and an apparatus to upgrade the whole learning process [55]. Recently, with the growth of new modernized and net-based advancements students may interface with the web and sign in to explicit sorts of net recreations to take an interest effectively in interactive games [5].…”
Section: Technology In Educationmentioning
confidence: 99%
“…Perkembangan teknologi pada zaman sekarang menjadi salah satu bagian dari kebutuhan hidup manusia, salah satunya dalam bidang pendidikan (Raja & Nagasubramani, 2018;Stosic, 2015). Perkembangan teknologi dalam dunia pendidikan menuntut adanya penggunaan materi dan media pembelajaran dengan memanfaatkan teknologi (Sahin & Yilmaz, 2019;Seery, Canty, & Gumaelius, 2018).…”
Section: Pendahuluanunclassified